Genetic mapping identified three hotspot genomic regions and candidate genes controlling heat tolerance-related traits in groundnut - Sharma, Vinay; Gangurde, Sunil S.; Nayak, Spurthi N.; Gowda, Anjan S.; Sukanth, B.S.; Mahadevaiah, Supriya S.; Manohar, Surendra S.; Choudhary, Rakeshkumar S.; Anitha, T.; Malavalli, Sachin S.; Srikanth, S.N.; Bajaj, Prasad; et al. (Frontiers in Plant Science, 2023)
Groundnut or peanut productivity and quality have been impeded by rising temperatures in semi-arid environments. Hence, having an understanding of the effects and molecular mechanisms of heat stress tolerance will aid in tackling yield losses. In this context, a RIL population was developed and phenotyped for eight seasons at three locations for agronomic, phenological, and physiological traits under heat stress. A genetic map was constructed using genotyping-by-sequencing with 478 SNP loci spanning a map distance of 1961.39 cM. QTL analysis using phenotypic and genotypic data identified 45 major main effect QTLs for 21 traits. Intriguingly, three QTL clusters (Cluster-1-Ah03, Cluster-2-Ah12, and Cluster-3-Ah20) harbor more than half of the major QTLs (30/45, 66.6%) for various surrogate traits, explaining 10.4–38.6%, 10.6–44.6%, and 10.1–49.5% of phenotypic variance, respectively. Furthermore, important candidate genes encoding DHHC-type zinc finger family protein (arahy.J0Y6Y5), peptide transporter 1 (arahy.8ZMT0C), Pentatricopeptide repeat-containing protein (arahy.4A4JE9), Ulp1 protease family (arahy.X568GS), Kelch repeat F-box protein (arahy.I7X4PC), FRIGIDA-like protein (arahy.0C3V8Z), and post-illumination chlorophyll fluorescence increase (arahy.92ZGJC) were underlying three QTL clusters. The putative functions of these genes suggested, they might be involved in seed development, regulating plant architecture, yield, genesis and growth of plants, flowering time regulation, and photosynthesis. Our results could provide a platform for further fine mapping, gene discovery, and the development of markers for genomics-assisted breeding to develop heat-tolerant superior lines/varieties.